From Auto- to Allotransplantation: Immunomodulatory Protocol for Hand and Arm Transplantation - Lee, W. P. Andrew; Shores, Jaimie T.; Brandacher, Gerald (Journal of Reconstructive Microsurgery, 2018)
Aim To achieve a favorable risk–benefit balance for hand transplantation, an immunomodulatory protocol was developed in the laboratory and translated to clinical application.Methods Following donor bone marrow infusion into transplant recipients, hand and arm allografts have been maintained on low-dose tacrolimus monotherapy.Results Good-to-excellent functional recovery has been achieved in patients compliant with medication and therapy, thus restoring autonomous and productive lives.Conclusion The risk-benefit balance can be tilted in favor of the hand transplant recipients by using an immunomodulatory protocol with minimum immunosuppression.
Keywords: allotransplantation; bone marrow infusion; hand transplantation; vascularized composite allograft; immunomodulation